Relationship of body mass index and waist-hip ratio among dental interns, residents and dental practitioners - Poudyel, Pragati; Sharma, Samjhana (Journal of Chitwan Medical College, 2021)
Background: Obesity is common global problem associated with co-morbid condition such as diabetes and hypertension. There is change in fat distribution pattern in both male and female during the process of aging. Body mass index along with waist circumference, waist-hip ratio and waist to height ratio are major anthropometric measures used to define the adiposity. This study aimed to assess the prevalence of overweight and obesity in individuals of different age-group’s as dental interns, residents, and dental practitioners. Methods: This cross-sectional study was conducted among 90 male and female subjects. Census method of sampling was used as all the interns, residents and dental practitioners were involved. Unstrectable measuring tape was used to measure waist circumference, digital weighing machine was used to measure weight and Standiometer was used to measure height as per world health organization guidelines. Body mass index was calculated from the weight of participants in kilograms divided by square of height in meters (kg/m2). Waist-hip ratio and waist to height ratio were calculated from measured data. Data was analyzed by Stastical Package for Social Sciences (SPSS) version 16. Results: Body mass index was found to be higher in male i.e 62.5% for overweight category compared to female where it was 24.2% and obesity was also higher among males while comparing with females. Waist circumference has significant correlation in male and female P<0.05. Waist hip ratio and different age groups also has positive correlation. Conclusions: Prevalence of overweight and obesity was seen among different age-groups and coherently the associated disease risk was explored.